Personality profiles and political regions: A latent profile analysis approach - Tianfang Yang; Xiaowen Xu (Current Research in Ecological and Social Psychology, 2024)
Big Five personality traits have been consistently shown to be important predictors of political differences. Other work found that political differences are related to geographical differences in personality. The present study extended existing work by examining the numbers and features of distinct personality profiles within different political regions of the United States using latent profile analysis (LPA). Across two large datasets (total N > 6,000), we found that while all regions shared similar numbers (3–5 profiles per region) and some overlapping patterns of personality profiles (e.g., well-adapted individuals), different political regions also showed unique personality profile patterns (e.g., “Worrisome Liberals”, “Rigid & Antisocial”). Overall, these results provide initial evidence suggesting that different personality profiles may exist among different political regions of the US, and offer insights on the interplay between personality, political ideology, and geographical differences.